(untitled) (Research, Society and Development, 2023)
One of the major obstacles in livestock farming is the low productivity of pastures due to the high degradation arising from poor land use and because our Brazilian soils are considered naturally acidic, characteristics that influence productivity. The aim of this study was to evaluate the use of organic Calcium (Ca) derived from algae of the genus Lithothamnium calcareum in pasture soils, and to verify its influence on the chemical profile of the soil, related to the parameters pH, Base Saturation, levels of Aluminum, Phosphorus (meh), Potassium, Ca and Magnesium (Mg) in the soil. The experiment was conducted at the Federal Institute of Education, Science and Technology of the Triângulo Mineiro - IFTM Campus Uberlândia. The design was in randomized blocks, with four treatments, applications equivalent to 0, 100, 200 and 300 kg of Lithothamnium.ha-1, and four repetitions. In 1m² plots, the organic Ca was applied manually in already established pasture without tilling. The application of organic Ca, solid Lithothamnium calcareum, promoted higher concentrations of Ca and Mg, although not different among the dosages of 100, 200 and 300 kg.ha-1Also, an increase in pH, an increase in the sum of bases, and base saturation (V%), and neutralization of Al were observed.